PROFESIONALISME GURU DALAM PERSPEKTIF ISLAM: INTEGRASI KOMPETENSI, MORAL-SPIRITUAL, DAN KODE ETIK PROFESI - Bunga Septia Nurul Fatikhah; Shofiatu Nadhifah; Soffy Nur Rofi’ah; Hani Nafiatul Ilma; Yasmin Putri Fathimah; Desti Widiani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT Teacher professionalism in Islamic education cannot be confined to mastery of instructional competencies alone, but also encompasses value-based integrity rooted in Islamic teachings. Previous studies have tended to examine professionalism and codes of ethics separately, resulting in the absence of a unified ethical framework. This study aims to formulate the concept of teacher professionalism from an Islamic perspective while also analyzing the role of ethical codes in shaping professional behavior. The study employs a qualitative approach through library research, utilizing thematic analysis of relevant scholarly literature and Islamic normative sources. The findings indicate that teacher professionalism consists of three main dimensions: academic-pedagogical competence, moral-spiritual integrity, and socio-professional ethics reflected in the consistent application of ethical codes. The code of ethics functions not only as a formal guideline but also as a medium for internalizing values within educational practice. This study proposes an integrative conceptual framework that positions professionalism and ethics as an inseparable unity in Islamic education. The findings highlight the importance of strengthening professional ethics education in developing teachers who are not only competent but also possess strong character and value-oriented dispositions. ABSTRAK Profesionalisme guru dalam pendidikan Islam tidak dapat dibatasi pada penguasaan kompetensi pembelajaran, tetapi juga mencakup integritas nilai yang bersumber dari ajaran Islam. Berbagai kajian sebelumnya cenderung membahas profesionalisme dan kode etik secara terpisah, sehingga belum menghasilkan kerangka etika yang terpadu. Penelitian ini bertujuan untuk merumuskan konsep profesionalisme guru dalam perspektif Islam sekaligus mengkaji fungsi kode etik dalam pembentukan perilaku profesional. Pendekatan yang digunakan adalah kualitatif melalui studi pustaka dengan analisis tematik terhadap literatur ilmiah dan sumber normatif Islam yang relevan. Hasil kajian menunjukkan bahwa profesionalisme guru tersusun atas tiga dimensi utama, yaitu kompetensi akademik-pedagogik, integritas moral-spiritual, dan etika sosial-profesional yang tercermin dalam penerapan kode etik. Kode etik tidak hanya berperan sebagai aturan formal, tetapi juga sebagai sarana internalisasi nilai dalam praktik pembelajaran. Penelitian ini menghasilkan kerangka konseptual integratif yang memposisikan profesionalisme dan etika sebagai satu kesatuan dalam pendidikan Islam. Temuan ini menegaskan pentingnya penguatan pendidikan etika profesi dalam pengembangan guru yang tidak hanya kompeten, tetapi juga berkarakter dan berorientasi pada nilai.